2000
DOI: 10.1002/(sici)1522-2586(200004)11:4<351::aid-jmri2>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic breast MRI with spiral trajectories: 3D versus 2D

Abstract: A three‐dimensional (3)D spiral sequence was developed for dynamic breast magnetic resonance (MR) imaging with much improved image quality. Partial Z phase encoding was applied to obtain thinner slices for a coverage of the whole breast. Comparison between the 3D and a previously developed multi‐slice 2D spiral sequences was performed on ten healthy volunteers without contrast and five breast patients with gadolinium‐diethylene triamine pentaacetic acid (Gd‐DTPA). The 3D spiral images had significantly less of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 22 publications
0
26
0
1
Order By: Relevance
“…Contrast-enhanced images were obtained using an interleaved rapid dynamic and highspatial-resolution protocol designed to capture the rate of enhancement as well as the morphologic features of any enhancing lesion during and after a single-bolus, antecubital, intravenous injection of 0.1 mmol/kg gadolinium contrast agent. 32 Initial dynamic imaging consisted of whole-breast, 3-dimensional spiral images 33 34 (TR, 33; TE, 9 msec; flip angle, 50 degrees; FOV, 20 cm; matrix, 512 ϫ 192 pixels; number of slices, 63; slice thickness, 1.5-2.0 mm; with water-selective, spectral-spatial excitation on resonance 1-2-1 MT suppression pulse). An additional 260 seconds of dynamic imaging were performed immediately after the high-resolution scan to capture the rate of wash-out of contrast from the breast.…”
Section: Mr Protocolmentioning
confidence: 99%
“…Contrast-enhanced images were obtained using an interleaved rapid dynamic and highspatial-resolution protocol designed to capture the rate of enhancement as well as the morphologic features of any enhancing lesion during and after a single-bolus, antecubital, intravenous injection of 0.1 mmol/kg gadolinium contrast agent. 32 Initial dynamic imaging consisted of whole-breast, 3-dimensional spiral images 33 34 (TR, 33; TE, 9 msec; flip angle, 50 degrees; FOV, 20 cm; matrix, 512 ϫ 192 pixels; number of slices, 63; slice thickness, 1.5-2.0 mm; with water-selective, spectral-spatial excitation on resonance 1-2-1 MT suppression pulse). An additional 260 seconds of dynamic imaging were performed immediately after the high-resolution scan to capture the rate of wash-out of contrast from the breast.…”
Section: Mr Protocolmentioning
confidence: 99%
“…Although the results of investigation to date have varied greatly, the sensitivity of breast DCE, T1-weighted MRI for malignancy has consistently been reported to be excellent (88-100%) (7)(8)(9)(10)(11)(12)(13)(14)(15). Qualitative analyses of the temporal changes in signal intensity following bolus CR injection have shown that malignant tissues generally enhance early, with rapid, large increase in signal intensity as compared with benign tissues.…”
Section: Backround and Rationalementioning
confidence: 99%
“…This is presumably due to the inherent leakiness of the tumor vasculature and/or increased vascularization. However, the specificity of DCE MRI has been rather variable, ranging from 37-97% (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Recently, T2 * -weighted perfusion MRI (17)(18)(19), as well as the technique of 1 H MR spectroscopy (MRS) (20)(21)(22) have also been examined as promising tool for improving the specificity of breast malignancy detection.…”
Section: Backround and Rationalementioning
confidence: 99%
“…Numerous methods exist for the implementation of each of the above steps: T1 and M 0 maps can be acquired with several techniques; [3][4][5][6] different mathematical models can be used to analyze the dynamic data; [7][8][9][10][11][12][13][14] and finally, various pulse sequences differing in sampling strategies and acquisition parameters have been developed to sample the signal in k-space. [15][16][17][18] The vast majority of preclinical sampling strategies used for DCE-MRI acquire a limited number of relatively thick slices. Volume averaging and limited coverage make it difficult to characterize the heterogeneity in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%